2014
DOI: 10.1155/2014/595724
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bluetongue Virus in Dairy Herds with Reproductive Problems in Sudan

Abstract: The objectives of this cross-sectional study were to determine the seroprevalence of blue tongue virus (BTV) and assess potential risk factors associated with BTV infection in dairy cattle with reproductive problems in Sudan. Serum samples were collected from a total of 784 animals from 37 herds and tested for antibodies against BTV using cELISA. A total of 663 out of 784 (84.57%) sera tested proved positive for BTV antibodies in all farms tested in Khartoum and Gazira States. The prevalence of antibodies was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In addition, Kassala state shares long international borders with Eritrea with no strict restriction on animals' movement across the borders which may allow introduction of infected animals into the localities. Similar high seroprevalence of BTV infection in various animal species was reported in several states in Sudan [ 28 , 29 , 31 , 36 , 39 ] and in countries around or near Sudan such as Libya (48.4%) [ 44 ]; Egypt (16.9%) [ 45 ]; Ethiopia (30.6%) [ 42 ]; and Saudi Arabia (47.3%) [ 46 ]. In addition, earlier epizootiological surveys also showed high prevalence rates for BTV seropositivity in Iran (93.5%) and Southern Turkey (88%) [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, Kassala state shares long international borders with Eritrea with no strict restriction on animals' movement across the borders which may allow introduction of infected animals into the localities. Similar high seroprevalence of BTV infection in various animal species was reported in several states in Sudan [ 28 , 29 , 31 , 36 , 39 ] and in countries around or near Sudan such as Libya (48.4%) [ 44 ]; Egypt (16.9%) [ 45 ]; Ethiopia (30.6%) [ 42 ]; and Saudi Arabia (47.3%) [ 46 ]. In addition, earlier epizootiological surveys also showed high prevalence rates for BTV seropositivity in Iran (93.5%) and Southern Turkey (88%) [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 75%
“…In Sudan, an early serological survey showed that BT infection is generally widespread among all domestic ruminants [ 27 ]. Subsequent serological surveys for BTV group-specific antibodies further confirmed the widespread nature of the infection in various parts of the country [ 28 , 29 , 31 , 36 , 39 ]. The present study showed that the overall seroprevalence of BTV group-specific antibodies in sheep and goats in Kassala state was substantially higher than previously recorded in other regions of Sudan.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is not surprising, because older cattle have had more time for exposure to BTV than younger animals. Studies in other countries have also shown higher seroprevalence in older cattle (17,18,19,20,21).…”
Section: Discussionmentioning
confidence: 87%
“…Bluetongue causes huge economic losses to the sheep industry due to high mortality and morbidity, as well as the trading of animals associated with its outbreak. The prevalence of bluetongue was 19% in Italy [ 26 ], but in Sudan, the prevalence has been as high as 94% [ 27 ]. In 2007, the cost of the bluetongue disease for sheep breeding farms in the Netherlands was estimated at 12.6 million euros [ 28 ].…”
Section: Farm Animal Diseases: Influence Prevalence and Controllmentioning
confidence: 99%